On The Digital Singularity - Bernardo Nejaim; Ilya Novikov (International Journal of Law in Changing World, 2022)
The present paper focuses on the analysis of bibliography, jurisprudence and case studies internationally such as Bragg v Linden Labs, forming an analysis of the obstacles for the recognition of virtual property as well as providing arguments for it’s acknowledgment on a multitude of legal systems internationally, all the while incentivizing the debate for its implementation with the use of a set of doctrines and directives. For this purpose, we will make comparisons of the different concepts of property on an international scale through the analysis of a host of different doctrines and jurisprudence from the United States, Europe, Russia and Brazil, aiming to demonstrate the resilience or acceptance of this concept of property. Finally, we will present at the end of this article the aforementioned directives that will serve to guide future discussions and implementations of virtual property.